Sanatorium pod Klepsydrą - Schulz, Bruno 1892-1942; Maksymiuk, Jerzy 1936- (DMMS-media distribution, 2013)
Set in pre-World War II Poland, a man visits the sanatorium where his father is dying and enters the surreal world where he relives some of his past and encounters strangeness at every turn
Original: Polen 1973
[Special features: photo gallery, before and after restoration views]
Bildformat 1.85:1 (16:9)
"Ein junger Pole reist zu seinem sterbenden Vater. Während der Reise wird auf verschiedenen Zeitebenen und im Wechsel zwischen Realität und Phantasie seine Geschichte erzählt. Die privaten Erinnerungen und Träume verknüpfen sich mit dem gesellschaftlichen Bild Polens vor dem Zweiten Weltkrieg. Ein phantastisch-poetischer Film nach Texten des Schriftstellers Bruno Schulz, voller Symbolik und atmosphärisch dicht erzählt." [filmdienst.de]
Keywords: Sanatoriums / Poland / Drama; Fathers and sons / Poland / Drama; Fathers and sons; Manners and customs; Sanatoriums; Alltag, Brauchtum; Poland / Social life and customs / 1918-1945 / Drama; Poland; Polen; Film; Blu-Ray-Disc